2014
DOI: 10.1136/annrheumdis-2014-eular.1455
|View full text |Cite
|
Sign up to set email alerts
|

AB1145-HPR From the World of Children to the World of Adults - A Qualitative Interview Study

Abstract: Background Juvenile idiopathic arthritis (JIA) is a chronic disease affecting 1200 children in Denmark (1). Due to differences in the organization of the paediatric and adult setting, and a change in roles between the child and it's parents, the transition from the paediatric to the adult setting can be challenging for adolescents with JIA (2, 3). However, little is known about promotive factors for successful JIA transition since few studies have explored the patient perspective and perception in the field. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…40,41,46,50 A range of qualitative methodologies were represented in the studies: four studies were identified as qualitative, 40,41,[50][51][52] two as grounded theory, 46,47 two as phenomenological, 45,49 and two as qualitative descriptive. 44,48 Details of characteristics of these included studies, including their specific phenomena of interest, are shown in Appendix III.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…40,41,46,50 A range of qualitative methodologies were represented in the studies: four studies were identified as qualitative, 40,41,[50][51][52] two as grounded theory, 46,47 two as phenomenological, 45,49 and two as qualitative descriptive. 44,48 Details of characteristics of these included studies, including their specific phenomena of interest, are shown in Appendix III.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Dates of publication ranged from 2006 to 2020. 40,41,[44][45][46][47][48][49][50][51][52] Four studies (five papers) originated in the UK, 40,41,45,49,50 two in Canada, 44,48 two in Sweden, 46,47 one in Spain, 52 and one in the Netherlands. 51 A total of 143 patients and 47 parents participated across all studies.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations